Renewable energy in five South East Asian countries: Review on electricity consumption and economic growth - Bakhtyar, Bardia; Sopian, K.; Sulaiman, M.Y.; Ahmad, Siti Aznor (Elsevier B.V., 2013)
The present study is an archival-statistical overview of the possibility of renewable energy production in five South East Asian countries and their economic capacity. The five South East Asian countries under review are the Philippines, Thailand, Malaysia, Indonesia, and Singapore, all of which have a combined population of 420 million. This number is a little less than the population of 25 European countries.These five countries have created a large market in the world and have enjoyed significant economic growth in recent years.Tropical climate in the region facilitates the potential for using clean and green energies.This article clarifies the effective relation between energy capacities and economic indices in these countries and analyzes the results.Using a survey, the paper shows that despite the shortage of energy in these countries brought by their fast economic growth, the share of renewable energy in energy production is constantly declining and more reliance is still placed on fossil fuels for energy production.